A unified investigation into the tensile and compressive sensing performance in highly sensitive MWCNT/epoxy nanocomposite strain sensor through loading-dependent tunneling distance. (10th November 2022) - Xia, Xiaodong; Zhao, Shijun; Zhang, Juanjuan; Fang, Chao; Weng, George J.
Abstract: Remarkable discrepancy between the tensile and compressive sensing performance has been experimentally observed in highly sensitive strain sensors, but at present no existing micromechanics-based theory can explain such a difference. To this end, we will investigate the tensile and compressive gauge factors of MWCNT/epoxy nanocomposite sensors in a unified fashion via an electromechanically coupled homogenization scheme. The discrepancy between the tensile and compressive sensing performance is analytically revealed by the loading-dependent tunneling effect assisted with a unified strain-dependent tunneling distance between the adjacent MWCNTs. The predicted gauge factor and resistance change ratio of MWCNT/epoxy nanocomposite sensors are calibrated with two independent sets of experimental data ranging from the compressive to tensile loadings. The tensile gauge factor of MWCNT/epoxy nanocomposite sensors is revealed to be higher than the corresponding compressive one. The absolute values of tensile and compressive resistance change ratio both enhance with the MWCNT waviness, the strain loading and the height of potential barrier between adjacent MWCNTs. In addition, a low MWCNT volume concentration and MWCNT aspect ratio can attain the high tensile and compressive gauge factors for MWCNT/epoxy nanocomposite sensors. The present research can contribute to the accurate design, fabrication, and optimization of highly sensitive strain sensors. Graphical abstract: Image 1